Nocebo effects in the treatment of endometriosis - Peter Thiel; Matthew J Burke; Philippa Bridge-Cook; Mathew Leonardi (Reproduction and Fertility, 2021)
The current approach to treating endometriosis is often inadequate or intolerable for many patients. Until more effective therapies are available, we should aim to maximize the effectiveness of our current options. Optimization may be possible by reducing nocebo effects, which are the negative therapeutic effects not directly caused by a treatment. Awareness of these effects, how they arise, and the factors influencing them, is invaluable if we aim to limit their magnitude. The unique nature of endometriosis diagnosis and management is especially prone to nocebo effects due to multiple factors, including diagnostic delays, feelings of invalidation, social transmission of expectations, and persistent symptoms despite numerous treatments. This commentary discusses the origins of these effects in people with endometriosis, methods of limiting nocebo effects, and future research directions.